Combustion and emissions behaviour for ethanol–gasoline-blended fuels in a multipoint electronic fuel injection engine. Issue 4 (20th April 2016) - Qi, D.H.; Lee, C.F.
Abstract : The study investigated the combustion and emissions of a gasoline engine using ethanol–gasoline blends. The results indicated that the peak cylinder pressure of E10 is evidently lower, but that of E20 is identical to that of gasoline. At lower engine loads, the combustion velocity of gasoline is faster, and the peak heat release rate (HRR) is higher than that of the blends, but at higher engine loads, E20 shows faster combustion velocity and a little higher peak HRR. The brake thermal efficiency of the blends is almost similar to that of gasoline, but the brake-specific fuel consumption of the blends is slightly higher. With the increase in ethanol content in the blends, CO evidently decreases, HC slightly increases at high engine loads, and NOx depends on the engine operating conditions as well as the ethanol content. The acetaldehyde of the blends is evidently and the ethanol is slightly higher than that of gasoline.